Aplikasi Regresi Spasial untuk Mengkaji Faktor yang Mempengaruhi Kejadian DBD di Jawa Timur Tahun 2018 - Sonny Adhiwanta Farmanda Putra; Mahmudah (Media Gizi Kesmas, 2023)
Background: Dengue Hemorrhagic Fever (DHF) is still one of the main public health problems in Indonesia. In 2018 in East Java DHF cases reached 9,425 cases with an incident rate of 23.9 per 100,000 population. Dengue fever is classified as an infectious disease originating from animals, the transmission of which tends to be influenced by many regional factors such as population density, population mobility, urbanization, and community behavior. Objective: this study was to apply spatial regression to determine the factors of the incidence of DHF in East Java in 2018. Methods: This research that uses secondary data. The data was obtained from the 2018 East Java Health Office profile book and the East Java Central Statistics Agency. The variables taken are the incidence of dengue fever, population density, PHBS in the household, healthy homes, and availability of clean water. Analysis of the data used in this study is Spatial Regression. Result: this study get the R-square results from the Spatial Error Model (SEM) regression model of 0.3921 and the R-square results from the Autoregressive Model (SAR) regression model of 0.03824. Conclusion: this study is that there is a relationship between Population Density, PHBS, Healthy Homes, and Availability of Clean Water on the incidence of DHF. With the results of this study, the SEM method can estimate the effect of 39.21% on the incidence of DHF and the SAR model can estimate the effect of 38.24% on the incidence of DHF.